Modified release verapamil induced cardiogenic shock. Issue 11 (21st October 2005) - Nanda, U; Ashish, A; Why, H J F
Abstract : Cardiogenic shock due to acute myocardial infarction is commonly seen in the accident and emergency department. Refractory cardiogenic shock has been reported after a therapeutic dose of modified release verapamil with concomitant use of beta blocker, metoprolol, but not after a single therapeutic oral dose of modified release verapamil alone. We report what we believe to be the first case of potentially life threatening cardiogenic shock resulting from the myocardial depressant effect of a single therapeutic oral dose of modified release verapamil. The patient made a dramatic recovery minutes after an injection of intravenous calcium chloride. The case is a reminder of the negative inotropic effect of verapamil and how it should be treated.